Corruption of ant acoustical signals by mimetic social parasites: Maculinea butterflies achieve elevated status in host societies by mimicking the acoustics of queen ants - Thomas, Jeremy A (Landes Bioscience, 2010)
Recent recordings of the stridulations of Myrmica ants revealed that their queens made distinctive sounds from their workers, although the acoustics of queens and workers, respectively, were the same in different species of Myrmica. Queen recordings induced enhanced protective behavior when played to workers in the one species tested. Larvae and pupae of the butterfly genus Maculinea inhabit Myrmica colonies as social parasites, and both stages generate sounds that mimic those of a Myrmica queen, inducing similar superior treatments from workers as their model. We discuss how initial penetration and acceptance as a colony member is achieved by Maculinea through mimicking the species-specific semio-chemicals of their hosts, and how acoustical mimicry is then employed to elevate the parasite’s membership of that society towards the highest attainable level in their host’s hierarchy. We postulate that, if acoustics is as well developed a means of communication in certain ants as these studies suggest, then others among an estimated 10,000 species of ant social parasite may supplement their well-known use of chemical and tactile mimicry to trick host ants with mimicry of host acoustical systems.